Políticas de formação continuada de professores na perspectiva da inclusão na rede municipal de educação de Curitiba: 2006-2015 - Silva, Silvia Sofia Scheid da (2016)
This research’s general objective is to investigate the continued formation policy of teachers from the general class of regular education, from the perspective of the inclusive education, developed and implemented by the Municipal Secretary of Education of Curitiba City Council, State of Parana, from 2006 to 2015. Under this outlook, the target was to explicit how the continued formation is being provided to teachers from the general class of regular education in Curitiba, who have students being assisted by the multifunctional resource room, given the legal requirement to provide an inclusive education, in the context of the 2008’s National Policy of Special Education in the Perspective of Inclusive Education. The interest of researching the policies on continued formation of teachers from the general class of regular education follows the need and the daily struggle to teach everything to everyone. Because of that, the question chosen was how, given the quality and inclusive education speech, is the continued teacher’s formation being carried out? To answer to this issue semi structured interviews were performed with teachers from the general class of regular education, teachers from the Multifunctional Resource Room and professionals from the Coordinating Body of Special Needs Attendance (CANE, in the Portuguese acronym). The resources offered by the coordinating body from 2009 to 2015 were also mapped. Besides, studies were carried out on the Curricular Guidelines of the City of Curitiba: Special and Inclusive Education, Unabridged Education, Adult Education – 2006 to 2015, on the Guiding Document from the Federal Ministry of Education – National Policy of Special Education Under the Perspective of the Inclusive Education of 2008, which establishes the Multifunctional Resource Room and the Specialized Educational Servicing (AEE, in the Portuguese acronym). There were the following objectives: to get to know historical notes and conferences, guiding principles and legislation regarding inclusive education; to present teacher’s continued formation policies of the city of Curitiba, regarding Special Education and their relationship with those policies; to unveil the policies on teacher’s continued formation of the city of Curitiba, regarding Inclusive Education, according to the interviewed teachers. In the final considerations it’s highlighted: the formative courses on inclusive education never ceased to be offered, however, the offering of formative actions were little integrated to its social context, fragmented, and dissociated from any theory based on historical, sociological or philosophical fundaments, with no political observation to enable an educational care that promotes the acquisition of historically gathered knowledge. The interviewed teachers point out the internet as the formative source and prove themselves confused regarding the city council secretary’s policies. This it is concluded that the courses are not considered sufficient for the interviewed teachers. They don’t characterize them as continued formation. The teachers point out the internet as a research source and if they seek the information they want and understand as necessary when they receive the student with disabilities, they are aiming for a theory related to their daily practice.